THE ANALYSIS OF ORGANIC RICE CONTRACT FARMING IN CAMBODIA: A LESSON LEARNED FOR INDONESIA - Sari, Betti Rosita (Semarang State University, 2011)
Â This study examines organic rice contract farming inCambodiaand its impact on farmersâ livelihood. The studyâs objective is to gain a better insight of the terms and conditions of rice contract farming scheme inCambodia, and determine under what conditions contract farming could bring improvements to farmersâ livelihoods. This study contributes new research findings on contract farming practices and farmersâ livelihood due to organic-rice contract farming with a case study in Kampong Speu province,Cambodia.Rice contract farming is not widespread inCambodiaat present, but is expected to expand significantly in the near future. Contract farming can increase investment into agricultural and infrastructure in rural areas. Contract farming can also enable farmers to access credit, inputs, technical advice and information about market condition and pricing trends. Yet, the disadvantages of contract farming include loss of farmer bargaining power and a potential reduction in profit margins, increased emphasis on improving production quality, land consolidation in favor of participating contract farmers, and less secure livelihoods.In this study, the contract farming arrangements of Angkor Kasekam Rongroeung (AKR) Company is studied. A survey of 16 contract farmers and 20 non-contract farmers in Kampong Speu province has been undertaken to examine the AKR contract farming scheme arrangements and to identify farmerâs motivations to participate in contract farming and its impact on farmersâ livelihood.AKR rice contract farming improves farmersâ livelihood because they get a higher income and rice yields. Higher price, good rice seed, and access to market are the main reasons for farmers to participate in AKR contract farming. However, strict requirements, heavy penalties, poor extension services, and lack of information about the contract terms and conditions reduce farmersâ long-term participation in contract farming. In addition, contract farmers have less bargaining power to negotiate with the company due to the absence of a farmer association.Overall, the status of contract farming inCambodiaclearly points to the great potential for its expansion in the future. However, for this to be realized and for the benefits to be shared fairly between companies and the farmers themselves, the study concludes that issues about the role of the government, the regulatory framework, contract enforcement, and the formation of small-scale farmer organizations must all be addressed.